Analysis and optimization of the unpredictable transmission zero in X‐band filter design. Issue 3 (5th November 2016) - Jiang, Ying; Wei, Bin; Zheng, Tianning; Chen, Jiabin; Cao, Bisong; Jiang, Linan; Song, Xiaoke
Abstract: This article focuses on the common problem of uncontrollable transmission zero (TZ) in X‐band filter design. Using uniform impedance rectangular resonator (UIRR) to design an X‐band filter always results in an unpredictable TZ on the low‐frequency side of the passband, which greatly deteriorates the frequency selectivity of the filter performance. Electromagnetic coupling polarity analysis of the UIRR shows that the magnetic crosscoupling between nonadjacent resonators which is opposite to the main coupling plays a major role in the unpredictable TZ. By optimizing the UIRR from the loop structure with a small opening to the folded one, weak couplings between resonators are obtained. A high‐temperature superconducting filter at X‐band using folded UIRR resonator was designed and fabricated with a center frequency of 10.01 GHz and a bandwidth of 58 MHz, and the uncontrollable TZ has been removed successfully from the low‐frequency side of passband. The measured insertion loss is less than 0.4 dB and the return loss is greater than 15 dB.